The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/jf950652k
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Polyphenols in Fresh Tea Leaves and Associations of Their Oxygen-Radical-Absorbing Capacity with Antiproliferative Actions in Fibroblast Cells

Abstract: The polyphenols in various parts of the tea plant used in manufacture of tea products (young leaves, old leaves, and stem) were analyzed by HPLC. The young leaves (apical bud and the two youngest leaves) were found to be richer (2.7-fold) in polyphenols than old leaves (from the tenth to the fifth leaf). Also, the tea polyphenols were found to be higher (1.4-fold) in summer than in spring. Ten different types of commercial tea (manufactured tea), including unfermented, semifermented, and fermented tea, were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
166
0
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(199 citation statements)
references
References 20 publications
12
166
0
11
Order By: Relevance
“…In general, the obtained results confirm the higher TEAC value of unfermented green tea than of fermented black tea, which is in line with data found in literature [12,13,25], although some studies indicate a reverse trend [15] or lack of differences in the antioxidant properties of teas manufactured via different technological processes [1,23]. In case of earl grey tea, earlier studies indicated a smaller polyphenol content compared to green and black tea [23], which can be explained by a lower total antioxidant potential of earl grey tea, despite the bergamot oil content, renowned for its antioxidant properties [26].…”
Section: Comparison Of the Antioxidant Capacities Of Teassupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the obtained results confirm the higher TEAC value of unfermented green tea than of fermented black tea, which is in line with data found in literature [12,13,25], although some studies indicate a reverse trend [15] or lack of differences in the antioxidant properties of teas manufactured via different technological processes [1,23]. In case of earl grey tea, earlier studies indicated a smaller polyphenol content compared to green and black tea [23], which can be explained by a lower total antioxidant potential of earl grey tea, despite the bergamot oil content, renowned for its antioxidant properties [26].…”
Section: Comparison Of the Antioxidant Capacities Of Teassupporting
confidence: 91%
“…However, TEAC values obtained in this work are congruent with the values determined through the use of other research methods [1,10,23]. TEAC values found in literature varied between 143 and 3100 (µmol Trolox/100 mL) for black tea [1,10,16,21,24], between 480 and 6200 (µmol TE/100 mL) for green tea [16,17,21] and between 728 and 1205 (µmol Trolox/100 mL) for earl grey tea [17].…”
Section: Comparison Of the Antioxidant Capacities Of Teassupporting
confidence: 89%
“…Tea is the most widely consumed beverage worldwide and has become an important agricultural product (Benzie & Szeto, 1999;Lin, Juan, Chen, Liang, & Lin, 1996). Recent experimental studies have recognized that tea exhibits a significant health protecting activity due to its high polyphenol content (Manzocco, Anese, & Nicoli, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Malathion is also an ingredient in shampoos regulated by the United States Food and Drug Administration (FDA) to control head lice. The exposure to Malathion became an ongoing basis as there are residual amounts of organophosphorous pesticides have been detected in soil, vegetables, grains and other food products (Larc, 1983). Therefore, there is growing need to exogenous sources of antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Certain catechins are the most biologically active group of the polyphenols in tea components (Lin et al, 1996). Much evidence indicates that tea polyphenols have various biological activities including antifungal, antiinflammation, antimutagenic, antioxidative, anticarcinogenic, antitumor, antidiabetic effects, the lowering of plasma cholesterol and triglyceride levels and reduction of blood pressure and platelet aggregation in several systems (Wang et al, 1989;Ho et al, 1992;Chisaka et al, 1988;Al-Attar and Abu Zeid, 2013).…”
Section: Introductionmentioning
confidence: 99%